Scoping review of guidance on safe non-consultant medical staffing recommendations for UK acute hospitals - Susanne Smith; Hannah Gower; Natasha Joy Doran; Nermin Hamza (BMJ Open, 2025)
Objectives Modern healthcare is delivered by an increasingly multidisciplinary team, complicating workforce management. Patient safety inquiries have led to reports such as the Francis and Berwick reports (2013), which consistently emphasise the need for proper staffing to ensure patient safety. While nursing has seen progress with safe staffing guidelines, there remains a significant gap in guidance for medical staff. In the UK, consultants are the senior members of the medical profession who have achieved a Certification of Completion of Training (CCT) and are able to practice independently. The number of required consultants is based on population needs, and future consultant numbers are used to determine the number of doctor training positions. However, this approach often overlooks the specific staffing needs of individual hospitals, particularly regarding patient safety. Although a named consultant is responsible for patient care, the medical workforce that handles day-to-day operations in acute hospitals consists of a diverse group of staff who require varying degrees of supervision based on their competency and seniority. This group includes medical associates, such as physician associates, and resident doctors (formerly known as junior doctors) who themselves are a heterogeneous group needing different levels of oversight. As a result, the previous focus solely on consultant staffing requirements must be broadened to address the realities of patient care. At present, no single resource provides a comprehensive summary of staffing recommendations that includes all groups within the non-consultant medical workforce. This research aims to identify existing guidance for this part of the medical workforce to support healthcare management. The objectives of this study are, therefore, to identify guidance and recommendations for safe staffing levels from a patient safety perspective for non-consultant medical staff in UK acute hospitals.Design A scoping literature review was conducted and is reported following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews guidelines.Data sources This used five search strategies: internal website searches, Google Scholar searches, general Google searches, medical database searches via Ovid and a snowballing strategy.Eligibility criteria English-language resources published from 2015 to 2024 that provide specific guidance on safe medical staffing levels for National Health Service acute hospitals in the UK.Data extraction and synthesis Thematic analysis was employed to identify patterns in the diverse guidance discovered, using a hybrid approach that combined human and AI methods. The benefits and limitations of this method are discussed.Results The review yielded 10 703 resources, of which 10 met all eligibility criteria for analysis. Identified themes include staffing requirements, staffing recommendations and a tiered system approach.Conclusions Medical staffing is complex due to the varying roles and competencies involved. While some guidance exists, there is a clear need for more comprehensive recommendations that go beyond specific specialities. Future research should focus on developing a medical safe staffing tool and addressing the barriers to comprehensive guidance, both of which would enhance patient care.